2013
DOI: 10.5714/cl.2013.14.4.228
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of carbon nanotube growth termination mechanism by in-situ transmission electron microscopy approaches

Abstract: In this work, we report in-situ observations of changes in catalyst morphology, and of growth termination of individual carbon nanotubes (CNTs), by complete loss of the catalyst particle attached to it. The observations strongly support the growth-termination mechanism of CNT forests or carpets by dynamic morphological evolution of catalyst particles induced by Ostwald ripening, and sub-surface diffusion. We show that in the tip-growth mode, as well as in the base-growth mode, the growth termination of CNT by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Nevertheless, a widely accepted CNTs growth mechanism can be outlined as follows. Based on the state of metal catalyst and the diffusion way of carbon at high temperature, two different mechanisms including vapor liquid solid (VLS) and vapor solid solid (VSS) are proposed in two general cases, as shown in Figure 3a,b [23,24,25,26]. At high temperature, a carbon precursor is adsorbed and then decomposed on the surface of low-melting-point catalyst nanoparticles to form carbon atoms.…”
Section: Fabrication Growth and Characterization Of Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a widely accepted CNTs growth mechanism can be outlined as follows. Based on the state of metal catalyst and the diffusion way of carbon at high temperature, two different mechanisms including vapor liquid solid (VLS) and vapor solid solid (VSS) are proposed in two general cases, as shown in Figure 3a,b [23,24,25,26]. At high temperature, a carbon precursor is adsorbed and then decomposed on the surface of low-melting-point catalyst nanoparticles to form carbon atoms.…”
Section: Fabrication Growth and Characterization Of Cntsmentioning
confidence: 99%
“…Finally, the carbon atoms precipitate on the interface in the form of CNTs growth by a precipitation-nucleation-crystallization process. On the other hand, according to the interaction strength between catalyst particles and substrates, now there are generally two growth models of CNTs, which involve tip growth model and base growth model [25,26,29], as shown in Figure 4a,b. When the interaction strength between catalyst and substrate is weak, carbon precursor decomposes into carbon atoms on the top surface of a catalyst particle, then carbon atoms diffuse down through the catalyst, and CNTs grow from catalyst bottom, thus pushing the whole catalyst away from the substrate.…”
Section: Fabrication Growth and Characterization Of Cntsmentioning
confidence: 99%
“…In contrast, fewer Ni particles were observed on the tip of CNTs in CNT30 and CNT60. It is reported that CNT grafts by pushing up the metal particle (tip growth model) ( Figure 8a) or growing up with the metal particles rooted on the surface of the substrate (base growth model) ( Figure 8b) [17][18][19][20][21][22]. When the interaction strength between the catalyst and the substrate is weak, the carbon precursor decomposes into the carbon atom on the top surface of the catalyst particle, then the carbon atom diffuses down through the catalyst and the CNTs grow from the bottom of the catalyst, thus pushing the whole the catalyst away from the substrate.…”
Section: Resistance Welding Methods and Flexural Testmentioning
confidence: 99%
“…However, the carbon atoms firstly form the hemispherical dome on the top of the catalyst, which grows in the form of seamless cylindrical graphitic to form the CNTs. Hence, the catalyst fixes on the base to support the growth of the CNTs [17][18][19][20][21][22]. In addition, it is reported that when the deposition time of CNT increases, the weight of CNT also increases but the growth length rate of CNT slows down [12].…”
Section: Resistance Welding Methods and Flexural Testmentioning
confidence: 99%
“…We have therefore chosen to pursue this idea. Fortunately, the weak bonding between the carbonaceous materials and the substrate could be resolved by in-situ techniques [24][25][26]. To the best of our knowledge, no researches on in-situ growth of binary carbonaceous materials including 1D CNTs and 2D graphene simultaneously on conductive substrates as the transparent CEs for DSSCs have been reported so far.…”
Section: Introductionmentioning
confidence: 98%